Karakteristik Ekstrak Pewarna Alami Bunga Bugenvil (Bougenvillea glabra) Dengan Variasi pH Pelarut Dan Daya Microwave Metode Microwave Assisted Extraction - Ginting , Tesalonika; Wartini, Ni Made; Anggreni, Anak Agung Made Dewi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Bougainvillea (Bougainvillea glabra) has the potential to be a source of natural dyes, especially the pigment betacyine. The extraction of this compound can be done by various methods, one of which is Microwave Assisted Extraction (MAE). This study aims to determine the effect of solvent pH and microwave power on the characteristics of natural dye extract of bougainvillea flowers using the MAE method, as well as determine the best treatment of solvent pH and microwave power on the characteristics of natural dye extracts of bougainvillea flowers using the MAE method. The experimental design used was a factorial Group Random Design (RAK) with two factors, namely solvent pH consisting of pH 1; pH 1.62; pH 2.25 and microwave power consisting of 100 watts of power and 300 watts of power, with 6 treatment combinations with 3 groups based on the time of implementation. The data was analyzed using ANOVA and followed by Tukey's follow-up test using minitabs, and the determination of the best treatment was carried out the Effectiveness Index Test. The results showed that the pH of the solvent and the microwave power had an effect on the yield, total betacyine, redness level (a*), yellowness level (b*), and antioxidant capacity. The interaction between affects the yield, total betacyine, redness level (a*), and yellowness level (b*) of antioxidant capacity. The best treatment to produce natural dye extract of bougainvillea flowers using the MAE method based on the effectiveness index test was obtained from pH 2.25 and microwave power of 100 watts with a yield characteristic of 61.85%, total betayanin 21.84 mg/100g, antioxidant capacity of 388.50 mg GAE/100g, and color intensity (a*) 34.53; (b*)18,42